Automated targeting technique for single-impurity resource conservation networks. Part 1: Direct reuse/recycle - Ng, Denny K.S. (Animo Repository, 2009)
This pair of articles presents an optimization-based, automated procedure to determine the minimum resource consumption/target(s) for a single-impurity resource conservation network (RCN). This optimization-based targeting technique provides the same benefits as conventional insight-based pinch analysis, in yielding various targets for an RCN prior to detailed design. In addition, flexibility in setting the objective function is the major advantage of the automated targeting approach over a conventional pinch analysis technique. The model formulation is linear, which ensures that a global optimum can be found if one exists. In part 1 of this pair of articles, the model for direct material reuse/recycle is presented. Its application is then demonstrated for single, multiple, and impure external resources using several literature examples. Part 2 of this pair of articles extends the automated targeting technique for RCNs with waste-interception (regeneration) placement. © 2009 American Chemical Society.